OPINI PUBLIK TERHADAP PENERAPAN NEW NORMAL DI MEDIA SOSIAL TWITTER - AWAD BIN MUHAMMAD ALKATIRI; ZHAFIRA NADIAH; ADINDA NADA S. NASUTION (CoverAge: Journal of Strategic Communication, 2020)
Social media is popular with all ages, people in young and old age groups can access social media. Social media is a place for information and opinion exchange. Twitter is one of the social media that is actively used in Indonesia. The new normal phenomenon that is currently being applied is wanted to be further known by researchers by referring to the hashtag #newnormalindonesia on Twitter. Researchers want to find out how public opinion is formed based on the hashtag #newnormalindonesia on Twitter. This research uses the concept of public opinion which is categorized into positive, negative, and neutral. In the research method, researchers use quantitative content analysis, the analysis unit uses thematic analysis units with the operationalization of concepts using the concept of public opinion. Coding sheets are used as instruments in data collection techniques, then in testing the validity and reliability using inter-coder reliability. The results showed that the twitter posts with the #newnormalindonesia hashtag tendto be negative by not supporting the implementation of new normal.